Analytical Model for Deflections of Bonded Posttensioned Concrete Slabs - Min Sook Kim; Joowon Kang; Young Hak Lee (Advances in Materials Science and Engineering)
This paper presents a finite element analysis approach to evaluate the flexural behavior of posttensioned two-way slabs depending on the tendon layout. A finite element model was established based on layered and degenerated shell elements. Nonlinearities of the materials are considered using the stress-strain relationships for concrete, reinforcing steel, and prestressing tendons. Flexural testing of the posttensioned two-way slabs was conducted to validate the developed analytical process. Comparing the analytical results with the experimental results in terms of deflections, it showed generally good agreements. Also a parametric study was performed to investigate the effects of different types of tendon layout.